Quantifying Midbrain Serotonin Transporter in Depression: A Preliminary Study of Diagnosis and Naturalistic Treatment Outcome - Tsai, H. C.; Lin, S.-H.; Chen, P. S.; Chang, H. H.; Lee, I. H.; Yeh, T. L.; Chen, K. C.; Chiu, N. T.; Yao, W. J.; Liao, M.-H.; Yang, Y. K. (Pharmacopsychiatry, 2015)
Introduction: Serotonin may play an important role in the pathology of major depressive disorder (MDD). However, the relationship between serotonin transporter (SERT) availability and the medical outcome of antidepressant treatment is uncertain.Methods: In this naturalistic study, SERT availability (expressed as the specific uptake ratio, SUR) in the midbrain of 17 drug-free patients with MDD and 17 controls matched for age and gender was measured using SPECT with [123I]ADAM. The severity of MDD was measured by the Hamilton Depression Rating Scale before, and after 6 weeks of non-standardized antidepressant treatment.Results: A total of 12 patients completed the study. The SUR of the patients with MDD was significantly lower than that of the healthy controls. The SUR of SERT was not found to have a linear relationship with the treatment outcome; however, supplemental analysis found a curvilinear relationship between treatment outcome and the SUR of SERT.Discussion: The findings indicate that the SUR of SERT is lower in patients with MDD; however it did not predict treatment outcome in a linear fashion. Studies with larger sample sizes are required.
Keywords: ADAM; major depressive disorder; serotonin transporter; SPECT; treatment response